Risk Factors Of Mortality Among Hajj Pilgrims In SOC 1444 H Group - Amada, Safaya; Ningrum, Dina Nur Anggraini; Junaidi, Lili; Iqbal, Usman (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
Hajj is an annual international ritual because it is carried out every year and involves Muslims from various parts of the world. Based on data from Siskohatkes, in 2022 there was a decrease in the number of pilgrims who died, which is 101 pilgrims, while in 2023 there was 8 times increase to 856 pilgrims who died. In 2022, the number of pilgrims with SOC embarkation who died was 19 pilgrims, while there was a significant increase in the number of deaths of pilgrims by approximately 6 times with the number of 129 pilgrims who died. The purpose of this study was to determine the risk factors for death of pilgrims for SOC group. This study is an observational quantitative study with a nested case control research design. This research was conducted in Central Java Province and Yogyakarta Special Region Province during the Hajj period 1444 H (2023). The result is that cardiomegaly (p-value:0,009; OR: 2.058; 95% Cl: 1.195-3.543), disease history (p-value<0.001; OR: 0.242; 95% Cl: 0.155-0.377), overweight and/or obesity (p-value<0.001; OR: 0.460; 95% Cl: 0.302-0.700) have a significant impact on the mortality of the Hajj pilgrims. It is hoped that Semarang Port Health Office can carry out monitoring and give more attention towards pilgrims who have cardiomegaly.